Flow simulation of icon city cable tunnel ventilation / Katheres Murugesu - Katheres, Murugesu (2019)
The main concern in this project is the study and develop a ventilation system for Icon City Cable Tunnel. This is due to the fact the cables inside the tunnels generates heats as much as approximately 600C and these cables are laid in a 67.35-metre-length with 3 meter diameter tunnel. By using the Air Change Per-Hour (“AC/Hr”) with the tunnel designed, the velocities and air flow in tunnel were determined. To simulate the air flow at the interior of the tunnel, draw a 3D geometry by using Solidworks software. The velocities acquired had been used in the ANSYS Computational Fluid Dynamics software to determine the temperature at the mid of the tunnel at numerous velocities to decide the suitable speed and air flow for the tunnel ventilation system. The ambient temperature took as 330C which the common temperature of the region is where the tunnel is proposed to be built. All the results and findings are in the Conclusion and Recommendation section in this report.